2014
DOI: 10.9790/0853-13611620
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of impacted premolar in Iraqi sample

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…This finding is consistent with other studies previously reported (Kalaji et al, 2017;Ranjitkar et al, 2002;Sisman et al, 2012;Turkal et al, 2013). Although in other studies, significant differences were not detected between arches (Al-Ghurabi and Najm, 2012;Al-Hadi Hamasha and Darwazeh, 1998;Kannan et al, 2015;Patil et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with other studies previously reported (Kalaji et al, 2017;Ranjitkar et al, 2002;Sisman et al, 2012;Turkal et al, 2013). Although in other studies, significant differences were not detected between arches (Al-Ghurabi and Najm, 2012;Al-Hadi Hamasha and Darwazeh, 1998;Kannan et al, 2015;Patil et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…In both genders, in all dental arches and sides, the prevalence of pulp stones occurrence in second premolar teeth was significantly higher than that in the first premolar teeth (P<0.0001). However, other previous studies reported that the prevalence of pulp stones is more frequent in the first premolar teeth than in second premolar teeth (Al-Ghurabi and Najm, 2012;Gulsahi et al, 2009;Sisman et al, 2012).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation